Assessing the impact of COVID-19 interventions on the hand, foot and mouth disease in Guangdong Province, China: a Bayesian modeling study - Zhang, Li; Yang, Fen; Zhu, Zhihua; Zeng, Weilin; Rong, Zuhua; Hu, Jianxiong; Li, Xing; Zhao, Jianguo; Zeng, Biao; Li, Yihan; Quan, Yi; Zhang, Qian; et al. (Frontiers in Public Health, 2024)
Background The non-pharmaceutical interventions (NPIs) against COVID-19 may have affected the transmission of hand, foot and mouth disease (HFMD). We aimed to assess the impact of the NPIs on HFMD in the high epidemic area of HFMD, Guangdong Province. Methods The data of HFMD cases, etiological information, and meteorological factors in Guangdong from January 1, 2012, to December 31, 2021, were collected. Using a Bayesian structural time series (BSTS) model integrated counterfactual framework, we assessed the effect of NPIs on HFMD by different intervention periods, populations (gender, age, occupation), and cities. We further explored the correlation between the reduction of HFMD and socioeconomic factors in 21 cities. Results A total of 351,217 HFMD cases were reported and 455,327 cases were averted in Guangdong Province during 2020–2021 with a reduction of 84.94% (95%CI: 81.63–87.22%) in 2020 and 29.49% (95%CI: 15.26–39.54%) in 2021. The impact of NPIs on HFMD differed by age and gender. The effects of NPIs were more remarkable for children aged 0–2 years and scattered children. We found that the relative reductions in 21 cities were related to the composition ratio of children and COVID-19 incidence. Conclusion The reduction of HFMD incidence was significantly associated with COVID-19 NPIs, and school closure was an effective intervention to prevent HFMD outbreaks. Our findings will contribute to the development of HFMD prevention and control measures.